Food Fortification and Supplement Use—Are There Health Implications?. Issue 13 (2nd October 2016) - Datta, Mridul; Vitolins, Mara Z.
Abstract : Dietary supplements are a multi-billion dollar industry in the U.S., and their use is increasing exponentially. Additionally, many foods and beverages are increasingly being fortified with single or multiple vitamins and minerals. Consequently, nutrient intakes are exceeding the safe limits established by the Institute of Medicine. In this paper, we examine the benefits and drawbacks of vitamin and mineral supplements and increasing consumption of fortified foods (in addition to dietary intake) in the U.S. population. The pros and cons are illustrated using population estimates of folic acid, calcium, and vitamin D intake, highlighting concerns related to overconsumption of nutrients that should be addressed by regulatory agencies.